Fenton Degradation of Fast Green Dye - Mohammad Salim, Haydar A.; Omar, Jaafar A.; Dirbas, Amir T. (Science Journal of University of Zakho, 2017)
The degradation of commercial textile dye named fast green (FG) was investigated by Fenton reagent under different operating conditions in an aqueous solution. The operating conditions were amount of hydrogen peroxide (0.05, 0.1 and 0.15 mL), pH (2-12) and concentration of ferrous ion (10, 20 and 30 mg). The initial rate of degradation was affected by the concentration of Fenton reagents [Fe(II) and H2O2 solution]. The rate of degradation enhanced as the concentration of ferrous ion increased. As the ferrous ion concentration increased from 10 to 30 mg, the removal percent was increased from 73% to 89%, respectively, at 25 min of reaction time. Also, the removal percent of FG increased from 74 % to 81 % as the amount of H2O2 increased from 0.05 to 0.15 mL, respectively, at 25 min of reaction time. It was also found that at pH 3 removal percent reach maximum value with 91.8%.  The kinetic study of FG degradation was also studied in this work and the results indicated that the degradation kinetics of FG followed the first-order kinetic.
Keywords: Fenton’s Reagent; Dye; Water pollution; Fast green; Kinetic